Burn wound healing using adipose-derived mesenchymal stem cells and manganese nanoparticles in polycaprolactone/gelatin electrospun nanofibers in rats - Azin Shahmohammadi; Hadi Samadian; Saeed Heidari Keshel; Khodabakhsh Rashidi; Amir Kiani; Masoud Soleimani; Farjam Goudarzi (BioImpacts)
Introduction: Wound healing is a major therapeutic concern in regenerative medicine. The current study aimed to investigate the second-degree burn wound treatment in rats using rat adipose- derived stem cells (ADSCs) and manganese nanoparticles (MnO2–NPs) in a polycaprolactone/gelatin electrospun nanofiber scaffold. Methods: After the synthesis of nanoparticles and electrospinning of nanofibers, the SEM analysis, contact angle, mechanical strength, blood compatibility, porosity, swelling, biodegradability, cell viability, and adhesion assays were performed. According to the results, the PCL/Gel/5%MnO2-NPs nanofiber (Mn-5%) was determined to be the most suitable scaffold. The ADSCs-seeded Mn-5% scaffolds were applied as a burn wound dressing. The wound closure rate, IL-1β, and IL-6 level, hydroxyproline, and glycosaminoglycans content were measured, and the hematoxylin and eosin, Masson’s trichrome, and immunohistochemistry stainings were carried out. Results: Based on the results, in Mn+S (ADSCs+PCL/Gel/5%MnO2-NPs nanofiber) and N+S (ADSCs+PCL/Gel nanofiber) groups, the IL-6 and IL-1β levels were reduced, and the percentage of wound closure, glycosaminoglycans, and hydroxyproline content were increased compared to the control group (P<0.05). Also, the lowest amount of α-SMA was observed in these two groups, demonstrating stem cells' role in reducing α-SMA levels and thus preventing fibrosis. Moreover, the amount of α-SMA in the Mn+S group is lower than in the N+S group and, is closer to healthy skin. According to histology results, the best type of treatment was observed in the Mn+S group. Conclusion: In conclusion, the ADSCs-seeded PCL/Gel/5%MnO2-NPs scaffold demonstrated considerable therapeutic effects in burn wound healing.